Agricultural Science (Single Award) syllabus: Effective for examinations from May 1993 - Caribbean Examinations Council (Caribbean Examinations Council, 1993)
This syllabus which represents the subject as a valid component of a well-balanced general education curriculum is designed to provide i) the basis for post-secondary education and training in the subject. ii) some knowledge and skills which will allow the school leaver to practice in a mixed-farming setting.
Keywords: CXC syllabus